2010
DOI: 10.1088/0953-8984/22/46/465801
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic forces and localized resonances in electron transfer through quantum rings

Abstract: Abstract. We study the current flow through semiconductor quantum rings. In high magnetic field the current is usually injected to the arm of the ring preferred by classical magnetic forces. However, for narrow magnetic field intervals that appear periodically on the magnetic field scale the current is injected to the other arm of the ring. We indicate that the appearance of the anomalous -non-classical -current circulation results from Fano interference involving localized resonant states. The identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…For high energies the spectra in the ring of suspended graphene and graphene on WSe 2 are very close to each other. The spectrum has two series of periodic levels, with energies decreasing (growing) with magnetic field, which correspond to the states associated with a clockwise (anticlockwise) current in the ring and are localized near the outer (inner) edge of the ring [44,45] and having angular momentum parallel (antiparallel) to the external magnetic field [45,46]. In both series of states the spin is parallel to the z direction.The width of those states is of the order of 10 nm at φ = 0.0008φ 0 and decreases with growing magnetic field.…”
Section: B Closed Quantum Ring With Etched Edgesmentioning
confidence: 99%
“…For high energies the spectra in the ring of suspended graphene and graphene on WSe 2 are very close to each other. The spectrum has two series of periodic levels, with energies decreasing (growing) with magnetic field, which correspond to the states associated with a clockwise (anticlockwise) current in the ring and are localized near the outer (inner) edge of the ring [44,45] and having angular momentum parallel (antiparallel) to the external magnetic field [45,46]. In both series of states the spin is parallel to the z direction.The width of those states is of the order of 10 nm at φ = 0.0008φ 0 and decreases with growing magnetic field.…”
Section: B Closed Quantum Ring With Etched Edgesmentioning
confidence: 99%
“…The transmission function exhibits an asymmetric line shape which depends on the coupling between resonant and extended states. In particular, Fano resonances have been reported in semiconducting ring shaped structures under the presence of an * daiara@if.uff.br external magnetic field [24]. The resonances arise as consequence of the broken time-reversal symmetry of localized states and their interference with extended states through the semiconducting ring.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [37][38][39] for a ring attached to the wire showed the existence of bound states, which are bounded in the ring but with small amplitude at the intersection and almost no amplitude along the wire. However, this kind of bound state is not the localized state as we mentioned above.…”
Section: Introductionmentioning
confidence: 99%